SOBRAMFA 18 years – dreams, perseverance and enthusiasm in Medical Education - Cauê Mônaco (O Mundo da Saúde)
This article describes the history and the present circumstances of the practice of Family Medicine and its development as a medical specialty and an academic discipline in Brazil, and it describes how, along the last 18 years, a group of doctors (SOBRAMFA - Brazilian Society of Family Medicine), working with students, residents, and medical schools, make efforts to disseminate the philosophy of the specialty and secure its future in the country. These strategic actions aim to increase the prestige of the specialty in schools and in medical labor markets. They arise the interest among Brazilian and foreign students through programs of fellowship of short and long duration, support family doctors in their daily life of real work and diverse environments of practical apprenticeship: home visits, outpatient departments, hospitals and “rest houses”, which include opportunities for apprenticeship and pedagogic Innovations in the many different areas of care, such as chronic patients and those affected by comorbidities, palliative care, women’s health and pre-surgery evaluations. In these programs we promote a broad debate about the humanist perspectives of Family Medicine, the maintenance of the passion and idealism in the practice, the medical perspective of care centered in the person, the development of inquiries about the daily routine of the family doctor, learning skills for ineducation use, updating the scientific literature and its application in decision-making, the development of competences of leadership and ways for balance technological and humanistic components of the medical practice.